Changes in toxicity and adsorbable organic bromine concentrations in ozonated reclaimed water irradiated with sunlight. (15th February 2023) - Wu, De-Xiu; Wang, Wen-Long; Du, Ye; He, Liu; Wu, Qian-Yuan
Highlights: Irradiation with sunlight degraded organic bromine compounds in ozonated water. Irradiation with sunlight decreased the cytotoxicity of ozonated water. Adsorbable organic bromine compound decreases and cytotoxicity decreases correlated. UV in sunlight dominated the adsorbable organic bromine and toxicity decreases. Abstract: Disinfecting reclaimed water for safe reuse can produce toxic disinfection by-products such as adsorbable organic bromine (AOBr). Irradiating stored reclaimed water with sunlight is a "green" and free method for eliminating some toxic disinfection by-products, but the effects of irradiation with sunlight on ozonated reclaimed water containing bromide are not well understood. In this study, AOBr was found at concentrations of 171–180 (µg Br)/L in ozonated reclaimed water containing bromide at a concentration of 2 (mg Br)/L and dissolved organic carbon at a concentration of ∼5 (mg C)/L. Irradiation with sunlight degraded 53–74% of the AOBr in two reclaimed water samples in 8 h, and the pseudo-first-order rate constants ( k ) were 0.09–0.17 h −1 . The concentration of tribromomethane, a typical Br-containing disinfection by-product, was decreased by >96% by irradiation for 8 h ( k = 0.42–0.47 h −1 ). Irradiation with sunlight decreased the toxicity of ozonated reclaimed water to Chinese hamster ovary cells. Irradiation with sunlight decreased the degree of intracellular oxidative stress and oxidative damage caused by ozonated reclaimed water. Irradiation with sunlight for 8 h decreased cytotoxicity of the ozonated reclaimed water samples by 79% and 65%. The change in AOBr concentration correlated with the change in toxicity (R 2 =0.69, p <0.05). The relationships between sunlight wavelength and decreases in the AOBr concentration and toxicity were assessed, and it was found that UV in sunlight was predominantly responsible for decreasing the AOBr concentration and toxicity by reclaimed water. During irradiation for 8 h, UV was responsible for 65%–66% of the decrease in the AOBr concentration and 65–79% of the decrease in reclaimed water induced cytotoxicity. Irradiation with sunlight is a promising method for degrading AOBr and detoxifying ozonated reclaimed water during storage to allow the water to be reused.